ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. H.M SAMPOERNA Tbk - Rorong, Angelie Priscilla (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This research of this study are based on the liquidity ratio proxied by Current Ratio and Quick Ratio, the condition of the company's financial performance is not good. Profitability ratio proxied by Net Profit Margin, Return on Assets, and Return on Equity, the company's financial performance is good. Solvency ratio proxied by Debt to Total Assets Ratio and Debt to Total Equity Ratio, the company's financial performance is good